RNA Profiling Analysis of the Serum Exosomes Derived from Patients with Active and Latent Mycobacterium tuberculosis Infection - Lv, Lingna; Li, Cuidan; Zhang, Xiuli; Ding, Nan; Cao, Tianshu; Jia, Xinmiao; Wang, Jinghui; Pan, Liping; Jia, Hongyan; Li, Zihui; Zhang, Ju; Chen, Fei; et al. (Frontiers in Microbiology, 2017)
Tuberculosis (TB) has exceeded HIV as the most lethal infectious disease globally for two consecutive years. Moreover, one third of the world’s population is estimated to have latent tuberculosis infection (LTBI). This is mainly because of difficulties associated with diagnosis and treatment for both TB and LTBI patients. Exosomes provide a promising research tool for TB diagnosis and treatment because they are released from various cells containing valuable biochemical information related to disease. In this study, we performed RNA-sequencing analysis on exosomes derived from clinical specimens of healthy controls (HC), active tuberculosis (ATB) and LTBI patients. Our results revealed the distinct gene expression profiles of the exosomes from LTBI and ATB patients. 1) We identified many distinct up-regulated and down-regulated differentially expressed genes (DEGs) in LTBI and ATB samples, and further screened the top-20 DEGs which might provide a potential panel for differentiation of HC, LTBI, and ATB. 2) We classified all the DEGs into six expression patterns, screened the top-20 genes in each pattern, and mainly focused on those highly expressed in LTBI and ATB. 3) Some Mycobacterium tuberculosis (Mtb) RNAs were only enriched in the exosomes of LTBI samples. 4) Pathway and function analysis further indicated an increase in deteriorating healthy signals in LTBI and ATB samples, including down-regulated signaling pathways/immune response and up-regulated apoptosis/necrosis. Our findings indicate the selective packaging of RNA cargoes into exosomes under different stages of Mtb infection, while facilitating the development of potential targets for the diagnosis, prevention and treatment of tuberculosis.